CUSTOMER PERCEPTIONS OF BANK SYARIAH INDONESIA MAGELANG SUDIRMAN SUB-BRANCH OFFICE FOR TELLER TRANSACTION SERVICES USING DIGITAL SYSTEMS - Dicky Setiawan; Risma Wira Bharata; Supanji Setyawan (Transpublika Publisher, 2022)
The aim of this study is to uncover the phenomenon underlying the slow growth and development of Bank Syariah Indonesia (BSI) customers in Magelang Sudirman Sub-branch Office. As such, the facts obtained will be more meaningful and can be used as a basis in developing Indonesian Islamic banking operations. The data analysis technique used is descriptive qualitative-interpretive conducted by controlled interviews through questionnaires. The population in this study were Magelang Sudirman Sub-branch Office customers in the Magelang area, Meanwhile, the sample in this research were Magelang Sudirman Sub-branch Office customers who deposit funds and/or borrow funds from Bank Syariah Indonesia Magelang Sudirman Sub-branch Office. Based on the results of research conducted, most of the informants stated that functionally digital teller services are very effective and make it easier for customers to carry out all types of banking transactions, because they are easy and fast to access.